2017
DOI: 10.1021/acsmacrolett.7b00374
|View full text |Cite
|
Sign up to set email alerts
|

Role of “Hard” and “Soft” Confinement on Polymer Dynamics at the Nanoscale

Abstract: We investigated the segmental dynamics of asymmetrically confined polymer films and report an unusual phenomenon in which the presence and thickness of a soft confining layer are responsible for significant changes in the segmental dynamics of the confined films. Specifically, the segmental dynamics of poly(vinyl alcohol) (PVA) thin films asymmetrically confined between hard aluminum (Al), and soft polystyrene (PS) films are shown to shift by as much as half an order of magnitude upon changes in the thicknesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…High-performance multicomponent materials have nanostructured morphologies where the desired global properties are obtained from an amalgam of local property changes caused by the multitude of internal interfaces. Studies on thin polymer films have demonstrated a host of property changes with decreasing film thickness attributed to interface effects, including polymer–polymer interfaces. The efficient design of multicomponent materials requires the understanding of how these interface effects perturb local properties. Glassy–rubbery interfaces between polymer domains impart material toughness and flexibility , and can be used to tune phononic transport .…”
mentioning
confidence: 99%
“…High-performance multicomponent materials have nanostructured morphologies where the desired global properties are obtained from an amalgam of local property changes caused by the multitude of internal interfaces. Studies on thin polymer films have demonstrated a host of property changes with decreasing film thickness attributed to interface effects, including polymer–polymer interfaces. The efficient design of multicomponent materials requires the understanding of how these interface effects perturb local properties. Glassy–rubbery interfaces between polymer domains impart material toughness and flexibility , and can be used to tune phononic transport .…”
mentioning
confidence: 99%
“…11,[15][16][17][18][19]22 Lang et al also perfomed molecular dynamics (MD) simulation study regarding the effects of polymer−polymer interaction energy and hardness of confining polymer on change in T g of confined polymers. i v i d u a l n o t d i r e c t l y a s s o c i a t e d w i t h s c i t e i s p r o h i b i t e d .…”
mentioning
confidence: 99%
“…In addition to polymer–solid and polymer–air interfaces, studies have recently focused on polymer structure and properties, such as T g and dynamics of nanoconfined polymers, near polymer–polymer interfaces. The contribution of the region near the polymer–polymer interface in polymer blend systems is not ignorable if the domain size is sub-100 nm, and the interface predominantly influences the overall blend structure and properties. , In this respect, understanding the local dynamics is clearly necessary. We have previously investigated the diffusion dynamics of PMMA/ d PMMA confined between graphene oxide (GO) sheets (GO/PMMA/ d PMMA/GO) using the neutron reflectivity (NR) technique .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with free surface and polymer–substrate interface, more complicated factors determine the polymer–polymer interfacial perturbation due to the diversity of polymers. Polymer–polymer interfacial perturbation has been studied mainly by stacking different polymer thin films or dispersing polymer nanoparticles in blends . Rharbi investigated the T g of emulsion polymerized PS nanospheres confined in cross-linked poly­(butyl methacrylate) matrices, and T g depression was observed when the particle size was decreased to below 50 nm .…”
mentioning
confidence: 99%